(untitled) (CIPEEX, 2025)
LibrasComThis project aims to create an innovative app for learning Brazilian Sign Language (Libras) in an interactive and playful manner. Structured like a game, the app offers practical activities, lessons, and an adaptive progress system for users at all levels. Its unique feature is the combination of gamification with a real-time translation tool using animated avatars, facilitating communication between deaf and hearing individuals. The app will also include an inclusive community, support for captions, and real-time feedback, ensuring an enriching and accessible learning experience.